Exploring the clinical utility of angioinvasion markers in papillary thyroid cancer: a literature review - Buczyńska, Angelika; Kościuszko, Maria; Krętowski, Adam Jacek; Popławska-Kita, Anna (Frontiers in Endocrinology, 2023)
Papillary thyroid cancer (PTC) is the most common type of thyroid cancer, and angioinvasion, the invasion of blood vessels by cancer cells, is a crucial pathological feature associated with disease progression and poor prognosis. Thus, a comprehensive search of scientific databases was conducted to identify relevant studies investigating angioinvasion markers in PTC. The selected studies were reviewed and analyzed to assess the clinical significance and potential utility of these markers in predicting angioinvasion and guiding treatment decisions. Numerous studies have investigated various markers associated with angioinvasion in PTC, including oxidative stress, vascular endothelial growth factor (VEGF), matrix metalloproteinases (MMPs), and other angiogenic factors. The results indicate that increased expression of these markers is correlated with the presence and extent of angioinvasion in PTC. Moreover, some studies suggest that these markers can serve as prognostic indicators and guide therapeutic strategies, such as selecting patients for more aggressive treatment approaches or targeted therapies. The findings from the reviewed literature highlight the potential clinical utility of angioinvasion markers in PTC. The identification and validation of reliable markers can aid in assessing the risk of angioinvasion, predicting disease progression, and optimizing treatment decisions for patients with PTC. However, further research and validation on larger patient cohorts are necessary to establish the robustness and generalizability of these markers in clinical practice.